The impact of Islamic educational management on teachers’ professional performance through Islamic teaching competence - Widodo Widodo (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose − examines the influence of Islamic education management on teacher professional performance with Islamic teaching competency as the mediator. Method – this study involved 295 madrasah teachers in Indonesia. The research data were collected through a Likert-scale survey. In addition to descriptive and correlational analyses, data analysis included Partial Least Squares-based Structural Equation Modeling (PLS-SEM). Findings − Islamic education management had a significant impact on Islamic teaching competency and teacher professional performance, Islamic teaching competency significantly influenced teacher professional performance, and Islamic education management influenced teacher professional performance through Islamic teaching competency.